2016
DOI: 10.1155/2016/5065703
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiota Determines Susceptibility to Experimental Autoimmune Uveoretinitis

Abstract: The microbiota is a crucial modulator of the immune system. Here, we evaluated how its absence or reduction modifies the inflammatory response in the murine model of experimental autoimmune uveoretinitis (EAU). We induced EAU in germ-free (GF) or conventionally housed (CV) mice and in CV mice treated with a combination of broad-spectrum antibiotics either from the day of EAU induction or from one week prior to induction of disease. The severity of the inflammation was assessed by fundus biomicroscopy or by his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
54
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 46 publications
4
54
0
2
Order By: Relevance
“…Within the eye, there was an increased proportion of Tregs in metronidazole‐treated animals as well. Similar results were obtained by another group who showed that altering the microbiome with either germ‐free rearing or treatment with oral metronidazole and ciprofloxacin resulted in reduced uveitis . At the National Eye Institute Horai et al demonstrated in transgenic mice that are engineered to express a retina‐specific T‐cell receptor, that an intestinal bacterial antigen was necessary for activation of retina‐specific T cells, implying that mimicry between a retinal and a commensal bacterial antigen might trigger uveitis …”
Section: Alterations In the Intestinal Microbiota Associated With Nonsupporting
confidence: 66%
See 1 more Smart Citation
“…Within the eye, there was an increased proportion of Tregs in metronidazole‐treated animals as well. Similar results were obtained by another group who showed that altering the microbiome with either germ‐free rearing or treatment with oral metronidazole and ciprofloxacin resulted in reduced uveitis . At the National Eye Institute Horai et al demonstrated in transgenic mice that are engineered to express a retina‐specific T‐cell receptor, that an intestinal bacterial antigen was necessary for activation of retina‐specific T cells, implying that mimicry between a retinal and a commensal bacterial antigen might trigger uveitis …”
Section: Alterations In the Intestinal Microbiota Associated With Nonsupporting
confidence: 66%
“…Similar results were obtained by another group who showed that altering the microbiome with either germ-free rearing or treatment with oral metronidazole and ciprofloxacin resulted in reduced uveitis. 17 At the National Eye Institute Horai et al demonstrated in transgenic mice that are engineered to express a retina-specific T-cell receptor, that an intestinal bacterial antigen was necessary for activation of retina-specific T cells, implying that mimicry between a retinal and a commensal bacterial antigen might trigger uveitis. 18 In further support of the importance of the intestinal microbiome in the uveitic process, our lab has found that exogenous administration of SCFAs, which are intestinal bacteria-derived fermentation metabolites of dietary fibre, can reduce the severity of uveitis through two mechanisms:…”
Section: Alterations In the Intestinal Microbiota Associated With Nmentioning
confidence: 99%
“…However, disease protection was reported in an analogous immunization-induced model of experimental autoimmune encephalomyelitis (EAE, a model for MS), as well as in a model of EAU, in mice raised under the GF conditions (9,15), further corroborating a role of gut microbiota in immunization-induced autoimmune diseases. Attenuated disease after a short-term course treatment with antibiotics was also reported in the model of EAE using the same antibiotic combination (16), or in the model of EAU on the C57BL/6J background with a different antibiotic combination (9). It is conceivable that the length and timing of antibiotic treatment that was used in different studies and/or specific microbial environments in various facilities may underlie these differences.…”
mentioning
confidence: 83%
“…While studies in uveitis patients are still underway, animal studies on autoimmune uveitis in rodents have unraveled strong associations of gut microbiota with disease. The examples include HLA-B27 transgenic rats, a model of spontaneous spondyloarthritis analogous to human ankylosing spondylitis (a disease known to be associated with uveitis), that exhibited altered microbiota compositions in the cecum compared to healthy controls (6), and the mouse models of spontaneous or induced uveitis, in which disease was strongly attenuated in the absence of gut microbiota (7-9). The latter will be discussed ahead with a particular focus on the recently published paper by Lin and colleagues in the July 2016 issue of IOVS (8).…”
mentioning
confidence: 99%
“…Uveitis is estimated to cause 10-15% of all cases of blindness in the US (Miserocchi et al, 2013). In recent years, host-microbiota interaction has been shown to contribute to both infectious and non-infectious uveitis, suggesting a common source of the two types (Heissigerova et al, 2016). Autoimmune uveitis activates both the innate and adaptive immune responses, where the causative ocular antigens are well characterized, and the multifactorial nature of the disease has been examined (reviewed in (Perez and Caspi, 2015)).…”
Section: Introductionmentioning
confidence: 99%